Smart textiles for medicine and healthcare : materials, systems and applications - Van Langenhove, L. (Woodhead publishing in textiles., 2007)
Smart or intelligent textiles are a relatively novel area of research within the textile industry with enormous potential within the healthcare industry. This book provides a unique insight into recent developments in how smart textiles are being used in the medical field. The first part of the book assesses trends in smart medical textiles. Chapters cover topics such as wound care materials, drug-based release systems and electronic sensors for health care. The second part of the book discusses the role of smart textile in monitoring the health of particular groups such as pregnant women, children, the elderly and those with particular physical disabilities. With its distinguished editor and team of international contributors, this book provides a unique and essential reference to those concerned with intelligent textiles in healthcare. Unlocks the significant potential of smart textiles within the healthcare industryProvides a unique insight into recent developments in this exciting field.